2011
DOI: 10.1128/jcm.02121-10
|View full text |Cite
|
Sign up to set email alerts
|

Gordonia bronchialis Bacteremia and Pleural Infection: Case Report and Review of the Literature

Abstract: Gordonia species are aerobic actinomycetes recently recognized as causing human disease, often in the setting of intravascular catheter-related infections. We describe a case of Gordonia bronchialis bacteremia and pleural space infection in the absence of an indwelling intravascular catheter and review the breadth of reported infections with this emerging pathogen. CASE REPORTA 52-year-old woman with a history of Hodgkin's lymphoma, prior splenectomy, and breast cancer was experiencing recurrent pleural effusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 27 publications
1
48
0
3
Order By: Relevance
“…bronchialis, the species isolated in this case, was initially identified from samples of soil and sputum from patients with pulmonary disease (Conville & Witebsky, 2001;Johnson et al, 2011;Siddiqui et al, 2012). Only 13 cases of infection with this species of actinomycete have been described (Siddiqui et al, 2012), including a reported recurrent breast abscess in an immunocompetent patient with no previous medical history (Werno et al, 2005) that shared many features with our case.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…bronchialis, the species isolated in this case, was initially identified from samples of soil and sputum from patients with pulmonary disease (Conville & Witebsky, 2001;Johnson et al, 2011;Siddiqui et al, 2012). Only 13 cases of infection with this species of actinomycete have been described (Siddiqui et al, 2012), including a reported recurrent breast abscess in an immunocompetent patient with no previous medical history (Werno et al, 2005) that shared many features with our case.…”
Section: Discussionmentioning
confidence: 50%
“…(Werno et al, 2005). Many patients, as in our case, require 6-12 weeks of therapy with different antibiotics, often along with appropriate surgical debridement (Johnson et al, 2011;Siddiqui et al, 2012;Sng et al, 2004;Werno et al, 2005). This prolonged course could be explained by the ability of Gordonia spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the previously reported cases of Gordonia bacteremia, many different antimicrobials were used, either alone or in a variety of combinations, including vancomycin, cephalosporins, carbapenems, TMP/SMX, and others (12). In our case, the patient did not respond to oral antimicrobials (TMP/ SMX and subsequently amoxicillin-clavulanate) until excisional surgical debridement was performed.…”
mentioning
confidence: 78%
“…bronchialis was first identified from samples of soil and sputum obtained from patients with pulmonary disease (20), and it is the causative organism in only a minority of human infections. It is a rare cause of bacteremia, usually in the setting of indwelling intravascular catheters (12). Only 13 cases of G. bronchialis infections in humans had been reported in our review of the literature (Table 1), and to our knowledge, this is the first reported case of osteomyelitis caused by this organism.…”
mentioning
confidence: 80%
“…Many Gordonia species has been isolated from soil [2] and Gordonia bronchialis has been detected in dogs [3], patients with sternal wounds [4], pleural fluid, tumor specimens, and skin [5, 6] among others.…”
Section: Introductionmentioning
confidence: 99%